THE METHOD AND PRINCIPLES OF AL-MARAGHI'S EXEGESIS - Ahmad Munirul Hakim (Jurnal Ushuluddin, 2026)
This article discusses the methods and principles of Tafsir al-Maraghi. The method employed in this article is library research. The findings of this study indicate that, methodologically, Tafsir al-Maraghi utilises the tahlili (analytical) method, which involves explaining the content of the Qur’anic verses in detail based on the order of the mushaf. As for the style or principles of interpretation used, these are adabi al-ijtima'iy (sociocultural and literary). Through this approach, al-Maraghi highlights the literary value and linguistic beauty (balaghah) of the Qur’an, whilst simultaneously using these verses as the primary instrument for addressing and resolving social issues. To further assist the reader, the structure of this exegesis is systematically organised, presenting groups of verses, explaining difficult vocabulary (syarh al-mufradat), providing an overall meaning, detailing the asbab al-nuzul, and minimising the use of complex grammatical and scientific terms.